The effects of workplace incivility and deviance on turnover intention and job performance among nurses in Pakistan - Faheem, Muhammad Asim (2017)
Health sector has a significant position in the services industry because it deals with the health of humans. Nurses are an indispensable part of the health sector, without their effective intervention; appropriate care of the patient is not possible to achieve. Therefore, the performance of nurses in health care settings is not compromised. Literature has identified that workplace incivility (cover and overt incivility) and workplace deviance (property deviance, production deviance, personal aggression and political deviance) can significantly influence employees’ performance (task and contextual performance), however, the mediating effect of turnover intention in this relationship can be an important contribution. Therefore, this study investigated the relationship of workplace incivility and workplace deviance with turnover intention, and job performance of nurses in the public health sector. In addition, mediating effect of turnover intention was investigated. A cross sectional study was conducted using a survey based research design and data was collected through questionnaires. Initially, 364 questionnaires were distributed to the nurses from public hospitals of Lahore, Pakistan, and 348 responded to the questionnaire. Participants of the survey were ensured of their anonymity and selected based on multistage sampling technique. Analysis using structural equation modeling found the relationship of workplace incivility and workplace deviance with turnover intention. Findings revealed that covert incivility, property deviance and personal aggression are significantly related with task performance. Moreover, overt incivility, property deviance, political deviance and personal aggression are significantly related with contextual performance. Finally, the findings revealed good support for the mediation hypotheses. In this study, turnover intention fully mediated the relationship of overt incivility, covert incivility and production deviance with task performance, while overt incivility, production deviance and political deviance mediated the relationship with contextual performance. Moreover, turnover intention partially mediated between political deviances with task performance. This study concluded that turnover intention significantly mediated the relationship between workplace incivility, workplace deviance and job performance.